Full-Length Sequence of Mouse Acupuncture-Induced 1-L (Aig1l) Gene Including Its Transcriptional Start Site. (17th February 2011) - Ohta, Mika; Sugano, Aki; Goto, Shuji; Yusoff, Surini; Hirota, Yushi; Funakoshi, Kotaro; Miura, Kenji; Maeda, Eiichi; Takaoka, Nobuo; Sato, Nobuko; Ishizuka, Hiroshi; Arizono, Naoki; et al.
Abstract : We have been investigating the molecular efficacy of electroacupuncture (EA), which is one type of acupuncture therapy. In our previous molecular biological study of acupuncture, we found an EA-induced gene, named acupuncture-induced 1-L ( Aig1l ), in mouse skeletal muscle. The aims of this study consisted of identification of the full-length cDNA sequence of Aig1l including the transcriptional start site, determination of the tissue distribution of Aig1l and analysis of the effect of EA on Aig1l gene expression. We determined the complete cDNA sequence including the transcriptional start site via cDNA cloning with the cap site hunting method. We then analyzed the tissue distribution of Aig1l by means of northern blot analysis and real-time quantitative polymerase chain reaction. We used the semiquantitative reverse transcriptase-polymerase chain reaction to examine the effect of EA on Aig1l gene expression. Our results showed that the complete cDNA sequence of Aig1l was 6073 bp long, and the putative protein consisted of 962 amino acids. All seven tissues that we analyzed expressed the Aig1l gene. In skeletal muscle, EA induced expression of the Aig1l gene, with high expression observed after 3 hours of EA. Our findings thus suggest that the Aig1l gene may play a key role in the molecular mechanisms of EA efficacy.